TAFSIR HURUF BA’ DALAM BASMALAH; PENDEKATAN TAFSIR ISYARI NAJMUDDIN AL-KUBRA - Ashani, Sholahuddin (Universitas Islam Negeri Sumatera Utara, 2020)
The Koran is not just a reading for Muslims, but should be a guide for all mankind. To use the Koran as a guide, a correct understanding is required through proper interpretation of the Koran. One of the interpretive approaches that tries to reveal the interpretation of the Koran is the interpretation carried out by the great Sufis, also known as the Isyari tafsir. Isyari interpretation has a unique approach but does not contradict the meaning of the birth of a verse in the Koran. This article aims to explore the interpretation presented by Shaykh Najmuddin al-Kubra with the isyari interpretation approach to the letter Ba’ in surah al-Fatihah. The interpretation of the letter Ba’ which he presented provides a profound message framed by ethical teachings to Allah and His creatures.